ON THE TEMPORAL VARIABILITY OF THE SEA SURFACE TEMPERATURE IN THE SOUTHWESTERN ATLANTIC BASED ON THE ANALYSIS OF "PATHFINDER AVHRR/NOAA" IMAGES - Teixeira, Carlos E. P.; Mata, Mauricio M.; Lentini, Carlos A. D.; Garcia, Carlos A. E.; Campos, Edmo J. D. (Revista Brasileira de Cartografia, 2009)
This study uses nine years of daily 9-km Pathfinder AVHRR/NOAA Sea Surface Temperature (SST) images to estimate the SST temporal variability of the southwestern Atlantic Ocean on time-scales ranging from sub-seasonal to inter-annual. First, we evaluated the annual and semi-annual deterministic signals in the total variability of the SST fields using a least-squares fit. We then removed the annual and semi-annual components from the original data and used a low-pass filter to estimate the contribution of the inter-annual component of total variability. Finally, the inter-annual signal was removed and the variance associated to the remaining residuals was calculated to address the intra-annual component. The annual signal was found to dominate over the area with a coefficient of determination higher than 85%, with amplitudes ranging from 1° to 13°C. The largest amplitudes were found on the continental shelf, with the highest values near the La Plata River estuary as a consequence of the river runoff. The semi-annual signal was significant near the Brazil/Malvinas Confluence (BMC), due to mesoscale activity with same periods. The Southern Annular Mode (SAM) appeared to be related to the high values of semi-annual amplitudes found close to 50º S, 65º W. The results for the oceanic area north of BMC showed that the region between 24°S and 32°S had semi-annual amplitudes close to 1.5°C. We suggested that this high amplitude was related to the South Atlantic Convergence Zone. The domain, as a whole, experienced weak inter-annual variations, except in the vicinity of the BMC where higher values (~1.2º C) were found. The Argentine shelf and the South Brazil Bight also presented significant inter-annual variability related to the inter-annual variations in the La Plata river discharge forced by ENSO events. The region close to the BMC and the South Atlantic Current were associated with high intra-annual variances due to intense mesoscale activity normally observed in these areas. Low intra-annual variance found in the Zapiola Drift was related to the anticyclone flow in this region which tended to isolate the circulation in the center of the drift. This gyre was forced by the meso-scale events of the BMC and the Antarctic Circumpolar Current that appeared as high values of intra-annual variance around the Zapiola Drift. The higher resolution SST data set, the longer time series and the larger domain permitted to identify new and important oceanographic features and to extend the results already reported in the southwestern Atlantic.